Μέτρηση της ενεργού διατομής των πυρηνικών αντιδράσεων Hf-174(n,2n)Hf-173 και Hf-176(n,2n)Hf-175 σε ενέργειες 15.3 MeV και 17.1 MeV - Σπηλιώτης, Αθανάσιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2015)
Purpose of this thesis, is the cross section measurement of nuclear reactions Hf-174(n,2n)Hf-173 and Hf-176(n,2n)Hf-175 for neutron beam energies of 15.3 and 17.1 MeV. The target used consisted of natural Hf. Measurement was made through neutron activation analysis method, using as a reference reaction. The neutron beam was produced at 5.5 MV Tandem Van der Graaf accelerator of NCSR Demokritos, by means of reaction. Tritium was bound in titanium which lied upon a surface of copper . For the measurement of the induced radioactivity of the samples, three HPGe detectors of relative efficiencies 100%, 50% and 16%, were used. Finally contribution of parasitic reactions Hf-174(n,γ)Hf-175 and Hf-177(n,3n)Hf-175 was evaluated in our results.